J. Hasselaar. Medical and ethical aspects of palliative sedation practice in the Netherlands. From controversy to guideline and beyond. - Janssens, Rien; Hasselaar, Jeroen (Tijdschrift voor Gerontologie en Geriatrie, 2010)
bespreking proefschrifJ. Hasselaar. Medical and ethical aspects ofpalliative sedation practice in theNetherlands. From controversy to guidelineand beyond.